Enhancing Interprofessional Relationships Between Nurses And Resident–Physicians In Graduate Medical Education - Agatha Parks-Savage; Linda R. Archer (European Scientific Journal, ESJ, 2016)
The culture of medicine in the United States has undergone and continues to experience substantial change. Those who provide medical education are being challenged to modify curricula and educational activities to engage residents and fellows in this new culture. In his 2007 Presidential Address to the Association of American Medical Colleges, Darrell Kirch, MD, spoke of the culture changes in medicine that are affecting the profession and the educational training programs. Academic medicine was historically defined as individualistic, autonomous, scholarly, expertcentered, competitive, focused, high-achieving, and hierarchical. The culture must now evolve to reflect collaboration, transparency, outcomes-focus, mutually accountable, team-based, service-oriented, and patient-centered. Knowing this, the culture of graduate medical education is now focusing on interprofessional skill building with its residents and fellows.